Arousal Facilitates Collision Avoidance Mediated by a Looming Sensitive Visual Neuron in a Flying Locust - Rind, F. Claire (American Physiological Society, 2008)
Locusts have two large collision-detecting neurons, the descending contralateral movement detectors (DCMDs) that signal object approach and trigger evasive glides during flight. We sought to investigate whether vision for action, when the locust is in an aroused state rather than a passive viewer, significantly alters visual processing in this collision-detecting pathway. To do this we used two different approaches to determine how the arousal state of a locust affects the prolonged periods of high-frequency spikes typical of the DCMD response to approaching objects that trigger evasive glides. First, we manipulated arousal state in the locust by applying a brief mechanical stimulation to the hind leg; this type of change of state occurs when gregarious locusts accumulate in high-density swarms. Second, we examined DCMD responses during flight because flight produces a heightened physiological state of arousal in locusts. When arousal was induced by either method we found that the DCMD response recovered from a previously habituated state; that it followed object motion throughout approach; and—most important—that it was significantly more likely to generate the maintained spike frequencies capable of evoking gliding dives even with extremely short intervals (1.8 s) between approaches. Overall, tethered flying locusts responded to 41% of simulated approaching objects (sets of 6 with 1.8 s ISI). When we injected epinastine, the neuronal octopamine receptor antagonist, into the hemolymph responsiveness declined to 12%, suggesting that octopamine plays a significant role in maintaining responsiveness of the DCMD and the locust to visual stimuli during flight.